Novel biconical antenna configuration with directive radiation - Shahpari, M.; Kashani, F.H.; Ameri Mahabadi, H. (2009)
In this paper a novel biconical antenna geometry has been proposed that has directive radiation pattern, higher gain and enhanced front to back ratio. Wide band performance is another characteristic of this new antenna.